Implementation of Puskesmas Accreditation and Protection of Patient Rights in Health Services at Puskesmas Rembang Regency - Intaningtyas Subawati; Endang Wahyati; C Tjahyono Koentjoro (Universitas Katolik Soegijapranata Semarang, 2020)
A Puskesmas or Health Center is one of the health service facilities having a duty of implementing health policies to achieve health development goals in its working area. Puskesmas is required to have accreditation every three years to ensure that quality and performance improvement and risk management implementation are continuously done. The accreditation is expected to guarantee the protection of the rights of the patients as service users of Puskesmas. There are 17 Puskesmas at Rembang District in which 94.1% of them have been accredited to see the degree of compliance with the Puskesmas accreditation standards.This study used a socio-legal approach having a descriptive-analytics specification. It used primary and secondary data meanwhile the data-gathering technique was conducted through field and literature studies. The data were then qualitatively analyzed.The results of the study showed that the accreditation to the Puskesmas of Rembang District was carried out according to the legislations of the Health Minister’s Regulation Nr. 75 of 2014 and the Health Minister’s Regulation Nr. 46 of 2015. One of the regulations on patient’s rights protection at Puskesmas was the Decree of Puskesmas Head regarding the patients’ rights to get services. The Puskesmas accreditation had been guaranteed the patients’ rights protection, but not optimally. Some factors were influencing the Puskesmas accreditation and the patients' rights protection to get health services at Puskesmas, namely juridical factors, technical factors, and other social factors.